Assessment the level of memory among elderly individuals residing in Nursing Homes in Lattakia city - الإبراهيم غسان; فاطمة قريط; بثينة الكردي (Latakia University Journal -Medical Sciences Series, 2024)
Memory declines in most elderly people, and early detection of memory impairment in the elderly is a helpful factor in preventing further aggravation of the condition by early initiation of treatment. The aim of research was to assess level of memory among elderly people residing in nursing homes in Lattakia city. Descriptive cross-sectional design was performed, and the research sample conducted of 40 elderly people who were selected randomization from the elderly in nursing homes. The research data was collected using a two-part tool, demographic data sheet and memory scale. The results revealed that more than half of the elderly had a weak level of memory, and a statistically significant relationship was found between the level of memory and age among elderly individuals. Therefore, the research recommended to conduct rehabilitation programs for the elderly individuals that stimulate memory by integrating the elderly individuals into mental and motor activities inside and outside nursing homes, and to provide a stimulating environment for the elderly inside nursing homes by providing audio-visual educational aids.